Alkali Metals‐Based Energetic Coordination Polymers as Promising Primary Explosives: Crystal Structures, Energetic Properties, and Environmental Impact. Issue 53 (27th August 2018) - Sun, Qi; Liu, Yang; Li, Xin; Lu, Ming; Lin, Qiuhan
Abstract: Coordination polymers (CPs) consisting of alkali metals (Na, K, Rb, and Cs) and a powerful nitrogen‐ and oxygen‐rich energetic ligand (4, 4′‐bis(dinitromethyl)‐3, 3′‐bisnitramide‐methylene‐furazanate, DBMF 2− ) were developed. Molecular structures of these CPs, confirmed by single‐crystal X‐ray diffraction analysis, indicated that the same ligand takes on a U‐shaped state for Na and an N ‐ shaped state for K, Rb, and Cs. Explosion tests demonstrated that both Na2 DBMF and K2 DBMF efficiently detonated the secondary explosive RDX. This indicates that they are both effective primary explosives. K2 DBMF exhibits better calculated detonation performance ( D : 8227 m s −1 ; P : 32.5 GPa) than the primary explosive Pb(N3 )2 . In addition, toxicity tests and evaluation of their decomposition products reveal their low impact on the environment. Both experimental results and theoretical analyses indicate that the combination of alkali metals and a powerful energetic ligand can stimulate the development of primary explosives. Abstract : Greener explosives : The combination of alkali metals and powerful nitrogen‐ and oxygen‐rich energetic ligands is an effective strategy of designing promising primary explosives. The coordination polymer with K exhibits a better calculated detonation performance ( D : 8227 m s −1 ; P : 32.5 GPa) than the primary explosive Pb(N3 )2 . In addition, toxicity tests and evaluation of the decomposition products reveal a lower impact on the environment (see figure).